New trends in mechanism and machine science from fundamentals to industrial applications - Flores, Paulo 1972-; Viadero, Fernando (Springer, 2015)
This work presents the most recent research in the mechanism and machine science field and its applications. The topics covered include: theoretical kinematics, computational kinematics, mechanism design, experimental mechanics, mechanics of robots, dynamics of machinery, dynamics of multi-body systems, control issues of mechanical systems, mechanisms for biomechanics, novel designs, mechanical transmissions, linkages and manipulators, micro-mechanisms, teaching methods, history of mechanism science and industrial and non-industrial applications. This volume consists of the Proceedings of the 5.